EXPRESSION OF P53 IN OVARIAN EPITHELIAL TUMOURS AND ITS CORRELATION WITH HISTOPATHOLOGICAL PARAMETERS - Abbasi, Fariba; Esmaili, Arefeh; Yekta, Zahra; Saffarifard, Abbas (Journal of Ayub Medical College Abbottabad, 2016)
Background: Ovarian cancers are the leading cause of death among gynaecologic neoplasms. The most common form of ovarian tumours is surface epithelial tumours divided as benign, borderline and malignant. Of particular interest are borderline tumours, because the pathologist may rely on some what vague morphologic criteria. The aim of this study was to evaluate the correlation of tumour suppressor protein P53 with macroscopic and microscopic criteria of ovarian surface epithelial tumours and distinction of borderline from malignant tumours. Methods: We studied 109 ovarian neoplasms including 74 benign, 8 borderline and 27 malignant ovarian epithelial tumours during March 2006-March 2011 in Urmia University of Medical Sciences. Immuno-histochemical staining for P53 performed on paraffin blocks and quantified with 12- point weighted score proposed by W.Y chan. Results: Mean P53 weighted scores in benign, borderline and malignant tumours were 0.20±0.63, 0.76±0.89 and 3.79±4.20, respectively. There was significant difference between malignant and borderline tumours(p=0.002) and between malignant and benign ones (p=0.000).None of 11 immuno-reactive benign and 4 borderline tumours showed P53 expression in > 50% of tumour cells, but 11 out of 15 immuno-reactive malignant tumours (73.3%) expressed p53 in >50% of tumour cells. P53 score significantly increases with mitotic count (p=0.000) and solidification of the tumour (p=0.001). There was no significant correlation with size (p=0.277), papillary structures (p=0.062) and grade (p=0.578). Conclusion: According to our results, P53 staining can be used as a helpful method in distinction of borderline from malignant ovarian epithelial tumours, especially in the manner that expression in >50% of cells favouring malignancy.